2019
DOI: 10.1088/1755-1315/406/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stomata, Chloroplast, and Chromosome of Local Mandarin Citrus (Citrus reticulata) Plants Grown from Endosperm Culture

Abstract: This research aimed to identify accessions of jeruk keprok Garut plants (Citrus reticulata) grown from endosperm culture with stomata analysis, chloroplasts analysis, and chromosome analysis. This research was conducted at the Plant Breeding Laboratory of Indonesian Citrus and Subtropical Fruits Research Institute (ICSFRI), Malang. This research used seven accessions of jeruk keprok Garut (local mandarin citrus) from endosperm culture and mother plant of Garut mandarin. Data analysis was carried out with the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Meanwhile, the lowest average number of stomata was found in chokun, 85.89, with a range of 73-94. The greater the number of stomata, the higher the stomata density and the closer the stomata are located to each other (Kosmiatin et al 2019). In this study, two groups of stomata number were found, a large number of stomata (101-200) and quite a lot (51-100).…”
Section: Leaf Paradermalmentioning
confidence: 44%
See 1 more Smart Citation
“…Meanwhile, the lowest average number of stomata was found in chokun, 85.89, with a range of 73-94. The greater the number of stomata, the higher the stomata density and the closer the stomata are located to each other (Kosmiatin et al 2019). In this study, two groups of stomata number were found, a large number of stomata (101-200) and quite a lot (51-100).…”
Section: Leaf Paradermalmentioning
confidence: 44%
“…The study showed that the highest average stomata length was found in fremont, 21.4 μm, with a range of 18.93-23.33 μm, while the lowest average stomata length was found in santang, 17.92 μm with a range of 17.91-18.25 μm. Stomata length is classified into 3 sizes: (i) Less long if the length of the stomata is <20 μm; (ii) Length if it has a length of 20-25 μm; and (iii) Very long size if the stomata length is >25 μm (Kosmiatin et al 2019). In this study, stomata length was catagerized into less long (<20 μm) and long (20-25 μm).…”
Section: Leaf Paradermalmentioning
confidence: 95%